Three doses evaluation of a microbial preparation obtained in Ecuador, in the productive and sanitary response of post-weaning pigs - Flores-Mancheno, Luis Gerardo; García-Hernández, Yaneisy; Proaño-Ortiz, Fredy Bladimir; Caicedo-Quinche, William Orlando (Universidad Pedagógica y Tecnológica de Colombia, 2015)
To evaluate three doses of a microbial preparation obtained in Ecuador (4x106 CFU of lactic bacterias, 1.5x105 CFU of yeast per milliliter), in the productive and health performance in pigs during the post-weaning stage, a completely randomized design was used, with four treatments and four replicates per treatment: T1 concentrated, T2, T3, T4 (concentrate plus 5 mL / kg of body weight (BW), 10 mL / kg BW, 15 mL/kg BW of microbial preparation, respectively). 160 barrows of the crossing Landrace x Large White with White Belgian x Pietrain, of 28 days of age and 6.99 kg of BW were used. The higher final body weight and the best gain of total and daily weight (P <0.0001) was obtained in the group of pigs in which 15 mL / kg BW of microbial preparation was added, with values of 25.78 kg, 18.78 kg and 447.25g, respectively. In the same experimental group more efficient conversions of dry matter, crude protein and metabolizable energy were found, 1.54 kg! kg BW and gain in body weight of 383.92 g/ kg BW and 23.16 Ml / kg BW, respectively. Also in this group the least presence of animals with diarrhea (P < 0,0001) 6.85% was recorded. It is concluded that the addition of 15 mL / kg BW improves the productive and sanitary performance of weaned piglets.